RCS measurements and results of an engine-inlet system design optimization. - Odendaal, J.W (IEEE Antennas & propagation magazine.)
A number of papers have been published on the prediction of backscatter from engine-inlet-type structures. Measured data used to verify these predictions mostly consists of backscattered data from canonical structures, e.g., cylindrical waveguide cavities. In this paper, measured backscattered data for an unmanned aerial vehicle-type engine-inlet system is presented. The effects of the application of radar-absorbing materials to the engine-inlet system on the contribution to the RCS is discussed, and data measured in a compact-range facility are presented.